ANTI-INFLAMMATORY ACTIVITY OF CRINUM DEFIXUM KER-GAWL (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
Crinum defixum Ker-Gawl is a bulbous herb which has a wide geographical distribution in India. It is commonly called Bon-naharu (meaning wild garlic) in Assam. Traditionally the bulb has been reported to have nauseant, emetic, emollient, diaphoretic properties and it is also used in various inflammatory conditions. The anti-inflammatory activity of the bulbs of the plants has been investigated in the present study in order to establish its traditional claims. The ethyl acetate, chloroform and ethanol extracts of bulbs of Crinum defixum were screened for anti-inflammatory activity by using carrageenan induced rat paw edema method. The study revealed that the ethyl acetate extract of the plant had significant anti-inflammatory activity than the chloroform and ethanol extracts. The study supports the ethanomedicinal use of this plant for inflammatory conditions.